Application of the Vienna Test System to measure training-induced changes in choice reaction time in U20 fencers: a 12-week training program pilot study - Teteris, L. E.; Saulite, S.; Licis, R.; Greve, M.; Boobani, B. (Sports, 2025)
This pilot study examined the effects of a 12-week reaction training program on physical and cognitive performance (choice reaction) in U20 Latvian fencers. Five qualified right-handed male fencers (aged 14.8-18.6 years) completed the Vienna Test System choice reaction task at baseline and after 12 weeks while cycling through five heart rate zones (1-5). Reaction speed (RS), motor speed (MS), choice reaction time (CR), and heart rate (HR) were recorded. Paired-sample t-tests indicated no significant group-level changes: RS (t = 1.46, p = 0.21, d = 0.65, 95% CI [-36.92, 118.92]), MS (t = 2.37, p = 0.07, d = 1.06, 95% CI [-3.14, 40.34]), CR (t = 1.70, p = 0.16, d = 0.76, 95% CI [-37.30, 156.26]), and HR (t = -2.69, p = 0.054, d = -1.20, 95% CI [-12.53, 0.17]). Individual responses revealed that three athletes improved CR in low- to moderate-intensity zones (-12.66% to -27.18%), whereas heart rate increased modestly (1.35% to 9.60%). Given the critical age for developing choice reaction, these findings should be considered as preliminary and exploratory, offering initial insights into how training might influence cognitive performance in young fencers and demonstrating that responses can differ across heart rate zones and among individuals.